The Effect of Labetalol or Remifentanil on Blood Pressure and Heart Rate after Laryngoscopy and Intubation - Azim Honarmand; Mohamadreza Savavi; Kimia Mirjalali (مجله دانشکده پزشکی اصفهان, 2017)
Background: The main aim of this study was to compare the effect of labetalol and remifentanil on blood pressure and heart rate after laryngoscopy and intubation in comparison with the control group.